Organic Molecules of Intrinsic Microporosity - McKeown, Neil B. (Organic Materials, 2020)
Organic molecules of intrinsic microporosity (OMIMs) are rigid molecules with an awkward shape that are designed to pack space inefficiently in the solid state maximizing free volume and thereby generating apparent microporosity as determined by gas adsorption. In this perspective article, the origin of the OMIM concept is explained and the progress in its realization both by synthesis and packing simulation is reviewed.
Keywords: Intrinsic microporosity; organic molecules; gas adsorption; packing simulations